2020
DOI: 10.34019/2596-3325.2020.v21.28893
|View full text |Cite
|
Sign up to set email alerts
|

Mites Macronyssidae Parasites of Passer domesticus (Linnaeus, 1758) (Passeriformes: Passeridae) in the Southern of Brazil

Abstract: The aim of this study was to report the species of haematophagous parasitic mites of Passer domesticus (Linnaeus, 1758) and analyze the infestation rates regarding to gender, body mass, and total length of the hosts. To do so, each of the 100 house sparrows captured in the urban area of Pelotas, Rio Grande do Sul, Brazil, was identified by gender, weighed, and measured. The mite collection was carried out after applying an ectoparasite-repelling talc in the body of the birds. Pellonyssus reedi was found in 29 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(26 reference statements)
0
2
0
1
Order By: Relevance
“…This mite has been isolated from hosts of various passerine families, e.g., in Corcoracidae, Furnariidae, Hirundinidae, Icteridae, Sturnidae, Thraupidae, Troglodytidae, and Tyrannidae, in Argentina (Arrabal et al, 2012), Brazil (Mascarenhas et al, 2009;Bassini-Silva et al, 2019), and Australia (Domrow, 1987), and it has also been found on various non-passerine birds -e.g., Accipitridae, Columbidae, Cuculidae, Laridae, Phasianidae, Picidae, Psittacidae, and Strigidae (Fonseca, 1948;Domrow, 1987;Aramburú et al, 2003;Mascarenhas et al, 2009;Arrabal et al, 2012;Coimbra et al, 2012;Santillán et al, 2015;Bassini-Silva et al, 2019;Mori et al, 2019). On the house sparrow, it has been found in Australia (Domrow, 1987), Brazil (Fonseca, 1948;Santos et al, 2020b), and North America (Fonseca, 1948). In spite of O. bursa being considered an important parasite of chickens in the Neotropics (Arrabal et al, 2012;Lareschi et al, 2017;Horn et al, 2018), there are no previous records on domestic fowl from Chile (Alcaíno & Gorman, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mite has been isolated from hosts of various passerine families, e.g., in Corcoracidae, Furnariidae, Hirundinidae, Icteridae, Sturnidae, Thraupidae, Troglodytidae, and Tyrannidae, in Argentina (Arrabal et al, 2012), Brazil (Mascarenhas et al, 2009;Bassini-Silva et al, 2019), and Australia (Domrow, 1987), and it has also been found on various non-passerine birds -e.g., Accipitridae, Columbidae, Cuculidae, Laridae, Phasianidae, Picidae, Psittacidae, and Strigidae (Fonseca, 1948;Domrow, 1987;Aramburú et al, 2003;Mascarenhas et al, 2009;Arrabal et al, 2012;Coimbra et al, 2012;Santillán et al, 2015;Bassini-Silva et al, 2019;Mori et al, 2019). On the house sparrow, it has been found in Australia (Domrow, 1987), Brazil (Fonseca, 1948;Santos et al, 2020b), and North America (Fonseca, 1948). In spite of O. bursa being considered an important parasite of chickens in the Neotropics (Arrabal et al, 2012;Lareschi et al, 2017;Horn et al, 2018), there are no previous records on domestic fowl from Chile (Alcaíno & Gorman, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Although A. globata is a nonspecific helminth (Rausch & Morgan, 1947;Mariaux, 1991), it should also be considered as a co-introduced parasite, but not co-invasive; this could change, if in the future, native hosts are found to be parasitized by this tapeworm (Lymbery et al, 2014). Additionally, whether or not O. bursa was co-introduced remains doubtful, because it is as a widely distributed parasite in the Americas (Mašán et al, 2014;Lareschi et al, 2017;Arce et al, 2018;Santos et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…Las observaciones fueron realizadas en un microscopio óptico AmScopeT690C-PL, 100X, habilitado con cámara MU1803-HS-CK-EA AMSCOPE. Para confirmar la especie fueron seguidas claves taxonómicas (Krantz & Walter 2009;Radovsky, 2010) y diversas publicaciones que muestran fotos de O. bursa (Bassini-Silva et al, 2022;Mesquita-Sousa et al, 2020;Ribeiro et al, 1992;Santos et al, 2020). Además, en julio 2022 se hicieron comparaciones de las preparaciones de RD con la colección de la Escuela Superior de Agricultura Luiz de Queiroz, ESALQ/ Universidad de Sao Paulo en el campus Piracicaba.…”
unclassified